Relevansi Pemikiran Imam Al-Asy'ari dan Imam Al-Maturidi Terhadap Penguatan Aqidah Ahlusunnah dalam Dunia Pendidikan Islam - Anis Salsabila; Sholihah Nurul Afifah; Rudi Ramdani; Anugrah Dimas Saputra; Yanto Maulana Restu (At-Tarbiyah Jurnal Pendidikan,Kebudayaan dan Keislaman, 2025)
This study aims to elaborate on the foundational thoughts of Imam Abu al-Hasan al-Ash‘ari and Imam Abu Mansur al-Maturidi and to analyze their relevance in the context of strengthening the creed of Ahl al-Sunnah wa al-Jama‘ah (Aswaja) within contemporary Islamic education, based on a review of recent scholarly articles published between 2020 and 2025. The findings indicate that both imams serve as the main pillars of Aswaja theology by offering a moderate approach that balances the authority of revelation (naql) and the role of reason (‘aql) as a response to classical theological extremism. The primary difference lies in determining the limits of reason: al-Ash‘ari prioritizes revelation as the source of moral and theological knowledge, while al-Maturidi provides greater space for human reason to recognize the existence of God. Furthermore, divergences are found in discussions on divine obligation (al-aṣlaḥ) and the concept of kasb (the acquisition of human actions), in which al-Maturidi tends to place greater emphasis on individual freedom. Overall, the theological thought of both schools remains highly relevant. Their concepts serve as the foundation of ‘aqidah curricula, promoting moderation (tawassuṭ) and critical thinking, thereby effectively safeguarding students from deviant ideologies and strengthening the stability of the Aswaja creed within Islamic educational institutions.